MOTIF PESERTA DIDIK BERPERILAKU KONTRADIKTIF TERHADAP LINGKUNGAN DI SMP NEGERI 35 SURABAYA - Safitri, Putri Eka; Jatiningsih, Oksiana (Kajian Moral dan Kewarganegaraan, 2024)
The living environment at school is a very important aspect of education. However, there are still students whose awareness needs to be increased regarding the importance of protecting the environment. The focus and aim of this research is to find out the "reason" and "purpose" motives behind students' contradictory behavior towards the environment at SMP Negeri 35, namely by using single-use plastics in schools that have the adiwiyata predicate. This research uses Alfred Schutz's phenomenological theory which discusses cause motives (Because Motive) and goal motives (In Order to Motive). The research method used is a qualitative approach with a phenomenological study research design, by exploring the meaning and values of the behavior of the six informants, namely students at SMP Negeri 35 Surabaya towards the environment. Data was collected through in-depth interviews with students and observation. The location of this research is at SMP Negeri 35 Surabaya in the Rungkut area, Surabaya. The data analysis technique used in this research refers to the approach developed by Miles and Huberman. This approach involves data collection, data reduction, data presentation, and drawing conclusions/data verification. The results of this research show that the "cause" and "purpose" motives of the informants include the Because Motive which encouraged the six informants to behave in contradictory ways by carrying single-use plastic packaging in the environment of SMP Negeri 35 Surabaya consisting of several main factors, namely family habits. , practicality, and the influence of the previous school environment. The goal motive (In Order to Motive) that the six informants at SMP Negeri 35 Surabaya wanted to achieve showed that the behavior of carrying single-use plastic packaging was driven by several goals, including carrying school supplies, seeking attention, saving time, energy and pocket money. It is hoped that the results of this research can help schools develop strategies to support students so that their behavior is more in line with the principles of adiwiyata schools.